Mental Fictionalism and Epiphenomenal Qualia. (24th August 2018) - Bács, Gábor
Abstract: In the paper I discuss and defuse Miklós Márton and János Tőzsér's phenomenological objection to mental fictionalism. The phenomenological objection states that mental fictionalism is phenomenologically undermotivated, because mental fictionalism is motivated by doubt in the existence of the subject matter of folk psychology but there undoubtedly exist conscious experiences which are subject matters of folk psychology. While one could argue, in the spirit of realist fictionalism, that mental fictionalism is not necessarily motivated by doubt in the existence of the subject matter of folk psychology, I choose a more direct approach. I defuse the phenomenological objection on the grounds that its premises cannot both be true, because conscious experiences which indubitably exist and conscious experiences which are subject matter of folk psychology are different things. In other words, their argument is either not sound or is invalid, because it commits an equivocation. So I defend mental fictionalism, but I am no mental fictionalist myself. I defend mental fictionalism, because I am against the idea of phenomenologically undermotivated theory of mind as such. The general point I want to make is that no theory of mind is phenomenologically undermotivated, that the metaphysics of mind is not on a short phenomenological leash.